Standardy postępowania diagnostycznego i terapeutycznego w nadciśnieniu tętniczym w różnych sytuacjach klinicznych - Gaciong, Zbigniew (Przewodnik Lekarza/Guide for GPs, 2008)
Hypertension is frequently associated with or complicated by concomitant disorders. The article presents standards of management of high blood pressure in patients with stroke, pregnancy, heart failure, and chronic renal diseases based on current ESH/ESC guidelines.